Low‐dose colchicine in type 2 diabetes with microalbuminuria: A double‐blind randomized clinical trial. Issue 10 (21st March 2021) - Wang, Yue; Peng, Xiaoqiong; Hu, Jinbo; Luo, Ting; Wang, Zhihong; Cheng, Qingfeng; Mei, Mei; He, Wenwen; Peng, Chuan; Ma, Linqiang; Gong, Lilin; Yang, Shumin; et al.
Abstract: Background: Neutrophil‐related chronic inflammation (NRCI) may contribute to the pathogenesis of diabetic kidney disease (DKD). We evaluated whether blocking NRCI with low‐dose colchicine prevents DKD. Methods: A double‐blind, randomized, placebo‐controlled study was conducted. A total of 160 patients with type 2 diabetes (T2D) and microalbuminuria (urinary albumin creatinine ratio [UACR] 30 to 300 mg/g Cr) who received angiotensin‐converting enzyme inhibitors (ACEi) or angiotensin receptor blockers (ARBs) for at least 3 months were included. Subjects were 1:1 randomized to a placebo or colchicine group (0.5 mg/day). Results: The primary end point was the incidence of overt nephropathy (UACR > 300 mg/g Cr). During the 36 months, 38 patients (51.4%) in colchicine group and 39 (54.1%) in the control group developed overt nephropathy (hazard ratio,  1.066; 95% confidence interval,  0.679‐1.673; P  = .78). Compared with placebo, colchicine modestly lowered levels of NRCI parameters ( P values <.05 for high‐sensitivity C‐reactive protein, white blood cell counts, neutrophil counts, and neutrophil‐to‐lymphocyte ratio), whereas the changes of UACR and estimated glomerular filtration rate (eGFR) were similar between the two groups. There were no significant differences between the two groups in drug‐related adverse events, including infection, gastrointestinal symptoms, and limb numbness. Conclusions: In patients with T2D with microalbuminuria, low‐dose colchicine effectively and safely lowered NRCI but did not prevent the incidence of overt nephropathy. Abstract : Highlights Low‐dose colchicine effectively and safely lowered NRCI in T2D patients with microalbuminuria. Low‐dose colchicine did not prevent the incidence of overt nephropathy. 摘要: 背景: 中性粒细胞相关性慢性炎症(NRCI)可能与糖尿病肾病(DKD)的发生有关。我们用低剂量秋水仙碱抑制NRCI并评估其是否能延缓DKD的发生。 方法: 本研究为一项双盲、随机、安慰剂对照临床试验。研究共纳入2型糖尿病合并微量白蛋白尿(肌酐比 [UACR] 30‐300mg/g Cr)的患者共160名, 所有患者均接受血管紧张素转换酶抑制剂(ACEi)或血管紧张素受体拮抗剂(ARBs)类药物至少3个月。患者按1:1随机分为安慰剂组或秋水仙碱组(接受秋水仙碱0.5mg/d)。 结果: 本研究的主要终点为显著肾病(UACR>300mg/g Cr)的发生率。在随访的36个月中, 秋水仙碱组的38名患者(51.4%)以及安慰剂组的39名患者(54.1%)发展成为了显著肾病(危险比1.066; 95%置信区间 0.679‐1.673; p=0.78)。秋水仙碱组与安慰剂组相比, NRCI水平有所下降(高灵敏C‐反应蛋白、白细胞总数、中性粒细胞总数、中性粒细胞‐淋巴细胞比值等指标, 两组有显著性差异, p<0.05), 但两组的UACR变化率、估算肾小球滤过率变化率无显著差异。两组的药物相关不良反应, 包括感染、胃肠道症状、肢体麻木等症状无显著差异。 结论: 在2型糖尿病合并微量白蛋白尿的患者中, 低剂量秋水仙碱能有效且安全地降低NRCI, 但是不能延缓DKD的发生。